Genetic polymorphisms of 20 STR loci in a Chaoshan group from Jieyang, China. (February 2019) - Huang, Enping; Guan, Tianshan; Li, Li; Xia, Pingping; Peng, Zhiyong; Feng, Chunlei; Chen, Ling
Highlights: Genetic polymorphisms of 20 STR loci in Jieyang were investigated. PowerPlex® 21 system (Promega, Madison, Wi, USA) was used to detect the genotypes. Jieyang Han population has close genetic relationship with the Fujian Han population. Abstract: We obtained allelic frequencies and forensic parameters of 20 short tandem repeat (STR) loci (D3S1358, FGA, D5S818, D7S820, CSF1PO, D16S539, D19S433, vWA, D8S1179, D18S51, D13S317, TPOX, TH01, D2S1338, D12S391, D1S1656, D21S11, D6S1043, Penta D, Penta E) from 529 unrelated individuals in Jieyang Han population using PowerPlex® 21 (Promega, Madison, Wi, USA). The relationship between the Jieyang Han group and other Han populations was studied and the results showed that the Jieyang Han population had the closest genetic relationship with the Fujian Han population.